The Expression of Apolipoprotein A1 on Pregnancy Outcome in Women with Polycystic Ovary Syndrome Compared to Fertile Women: A Cross-Sectional Study - Fathy H (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2016)
Objective: To explore the level of apolipoprotein A1 expression in human endometrial tissues in women with polycystic ovary syndrome compared to fertile women.  Patients and Methods: This was a cross sectional study performed at Ain Shams University Maternity Hospital, over a 2-year period, between Jan 2014 and Jan 2016, and included 80 women divided into two groups. Group I (n=40) with polycystic ovary syndrome who were presented at the infertility clinic and group II (n=40) fertile women who were presented due to any cause other than infertility as a control group. All women were scheduled for endometrial sampling by Endosampler. Participant ages ranged from 20 to 35 years. A written informed consent was obtained from all women before participation. Endometrial apolipoprotein A1 was investigated using ELIZA. Samples were obtained from all patients in the proliferative phase (just before ovulation when the dominant follicle is 20 mm) and secretory phase (5 days after the 1st sample).  Results: In this study, endometrial apolipoprotein A1 expression was up regulated in patients with polycystic ovary syndrome compared to normal subjects, also the level was higher in the proliferative phase when compared to the secretory phase (P value < 0.05).  Conclusions: It seems that differentially expressed apolipoprotein A1 negatively affects endometrial receptivity in patients with polycystic ovary syndrome. The results showed that apolipoprotein A1 level significantly changes in the human endometrium during the menstrual cycle with minimum expression in the secretory phase, coincident with the receptive phase (window of implantation).